Is Nanotechnology Helping in the Fight Against COVID-19? - Cardoso, Valéria Maria de Oliveira; Moreira, Bruna Juliana; Comparetti, Edson José; Sampaio, Isabella; Ferreira, Leonardo Miziara Barboza; Lins, Paula Maria Pincela; Zucolotto, Valtencir (Frontiers in Nanotechnology, 2020)
The novel coronavirus disease (COVID-19) pandemic represents an unprecedented public health concern. The disease, which has an incredibly high spreading rate, was discovered in late December 2019, in Wuhan, Hubei province, China. The virus that causes COVID-19, known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is responsible for the infection of more than 21.8 million individuals and more than 772 thousand deaths in 216 countries, numbers which are still rising. Currently, there are no vaccines or antiviral treatments officially approved for the prevention or treatment of COVID-19. Since its appearance, several therapeutic approaches have been tested, including the use of repurposing drugs, such as broad-spectrum antivirals, nucleoside analogs, protease inhibitors, immunomodulators, and plasma therapies, among others. However, these strategies have not shown great clinical benefits and are only administered to attenuate the symptoms. Although many therapeutic strategies are being tested against COVID-19, more efforts should be devoted to fighting the virus. Nanomaterials represent a powerful tool against COVID-19 since they can be designed to act directly toward the infection, increase the effectiveness of conventional antiviral drugs, or even to trigger the immune response of the patient. Advances in nanotechnology over the past decades allow us to develop new nanomaterials and step forward in the application of new technological tools. This review addresses aspects related to the structural characteristics of the virus, the mechanisms involved in the infection, and therapies that are currently used against COVID-19. This review discusses nanotechnology-based strategies for the prevention, diagnosis, and treatment of COVID-19, including nanomaterials for face masks and surface sterilization, adjuvants, vaccine delivery nanosystems, and point-of-care tests, providing a perspective on how nanotechnology could be an applied in the fight against COVID-19.